SENSORY CHARACTERISTICS OF A PINEAPPLE AND COCONUT-WATER-BASED SPORT DRINK - Setyaning, Ruth Surya Wahyu; Endrinikapoulos, Ariana (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Coconut water is a natural isotonic beverage that can provide effects comparable to commercial sports drinks in supporting physical performance and physiological responses. On the other hand, pineapple is a tropical fruit with natural anti-inflammatory properties, a sweet taste, and a distinctive, refreshing aroma, making it a potential enhancer of the sensory characteristics of sports drinks. This study aimed to develop a sports drink formulation based on coconut water and pineapple juice and to evaluate the sensory characteristics of the formulated beverages. Sensory evaluation was conducted with 38 panellists using a 4-point scale, and the data were analysed using ANOVA followed by Duncan’s Multiple Range Test. The difference in the proportion of coconut water and pineapple juice significantly affected the organoleptic parameters of colour (p<0.001) and aftertaste (p=0.011) but had no significant effect on aroma (p=0.450), taste (p=0.136), or overall preference (p=0.743). An increased proportion of pineapple juice in the formulation resulted in a brighter colour and a more pungent aftertaste in the sports drink. The selected formulation in terms of colour was Formula 3; meanwhile, Formula 1 was preferred for aftertaste.